The Influence of Socialization Activity in Group Therapy to Socialization Capabilities - Cipto Cipto; Siswoko Siswoko; Ajeng Titah Normawati (Jurnal Studi Keperawatan, 2020)
Social isolation is interpersonal relation disorders that caused by personal inflexibility, until maladaptive behavior and disturb the function of individual in relation. It isthe third largest mental disorder diagnosis in the hospital. This condition describe that it requirestherapiesfor decreasing cases. One of them is Socialization Activity in Group Therapy that facilitates clients doing socialization in group. The influence of Socialization Activity in Group Therapy to socialization capability in clients with social isolation was measured in this study. The method of it used experimental study with pretest and post-test one group design. Samples selected using purposive sampling(32 samples). In pretest, socialization capabilities of clients were assessed using GAT observation sheet, after that the intervention of Socialization Activity in Group Therapy was given every week until seven week for seven steps. At post-test, Socialization Activity in Group Therapy was evaluated using same tool in pretest. The result showed that the mean of socialization capabilities at pre-test was 2.73 and 6.70 at post-test, there was a statistically high significant difference with paired t-test at p 0,001 or 00,05 score.